2020
DOI: 10.3390/biomedicines8090320
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Core Signaling Pathways of Hepatitis B Virus Pathogenesis for Biomarkers Identification and Drug Discovery via Systems Biology and Deep Learning Method

Abstract: Hepatitis B Virus (HBV) infection is a major cause of morbidity and mortality worldwide. However, poor understanding of its pathogenesis often gives rise to intractable immune escape and prognosis recurrence. Thus, a valid systematic approach based on big data mining and genome-wide RNA-seq data is imperative to further investigate the pathogenetic mechanism and identify biomarkers for drug design. In this study, systems biology method was applied to trim false positives from the host/pathogen genetic and epig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 172 publications
(202 reference statements)
0
15
0
Order By: Relevance
“…Applications of DL to assist physicians and scientists in clinical settings using epigenomic data have been relatively unexplored until very recently. Except for one paper published in 2016, 21 out of 22 papers reviewed were published in the last 5 years and a majority of the models were developed by USA and China research teams [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. This suggests a novel field of study that gains an increasing interest.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Applications of DL to assist physicians and scientists in clinical settings using epigenomic data have been relatively unexplored until very recently. Except for one paper published in 2016, 21 out of 22 papers reviewed were published in the last 5 years and a majority of the models were developed by USA and China research teams [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. This suggests a novel field of study that gains an increasing interest.…”
Section: Resultsmentioning
confidence: 99%
“…Among human disease-related tasks, disease detection, subtype classification, and treatment response prediction received great concerns. Existing evidence indicated that DL models in epigenomics for solving the human disease-related tasks outperformed [ 23 , 24 , 29 , 41 ] or at least competitive to traditional ML models [ 37 ]. Some predictive models in previous studies utilized DL as a powerful component of a multi-step process [ 28 , 29 , 30 , 31 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations